2016
DOI: 10.1111/pan.13047
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative hypothermia in neonatal intensive care unit patients: effectiveness of a thermoregulation intervention and associated risk factors

Abstract: Perioperative hypothermia is a challenge in the care of neonatal intensive care unit patients; however, a thermoregulation intervention can decrease the incidence with sustained results. Future studies can examine why certain procedures have a tendency toward increased perioperative hypothermia, determine the relative value of quality improvement interventions, and characterize the morbidity and mortality associated with perioperative hypothermia in neonatal intensive care unit patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 9 publications
1
28
0
10
Order By: Relevance
“…To adjust for confounding, analysis was performed using clinically relevant, the variables was selected in advance, including age, sex, weight at surgery, birth body weight, gestation days, the length of surgical time and fresh gas flow rate. These clinically relevant variables were selected based on biologic plausibility and were the most popular reported confounders in cohort on neonates [12]. Variance inflation factors for all predictors in multivariable regression were chosen to 1.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To adjust for confounding, analysis was performed using clinically relevant, the variables was selected in advance, including age, sex, weight at surgery, birth body weight, gestation days, the length of surgical time and fresh gas flow rate. These clinically relevant variables were selected based on biologic plausibility and were the most popular reported confounders in cohort on neonates [12]. Variance inflation factors for all predictors in multivariable regression were chosen to 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…To date, some anesthesia providers attributed it to patients' age, weight and different surgical procedures. Actually, in 2017, Engorn et al did a retrospective research in neonates and revealed that gestation days, weight, type of surgery, sex, and length of surgery were not the risk factors for hypothermia except the thermoregulation interventions, which pointed that active and passive warming strategies played the pivotal role in maintaining normothermia [12]. A study with multiple logistic regression in Thailand showed that the following risk factors for core hypothermia included high ASA physical status and open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To adjust for confounding, analysis was performed using clinically relevant, the variables was selected in advance, including age, sex, weight at surgery, birth body weight, gestation days, the length of surgical time and fresh gas ow rate. These clinically relevant variables were selected based on biologic plausibility and were the most popular reported confounders in cohort on neonates [12]. Variance in ation factors for all predictors in multivariable regression were chosen to 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, moving critically ill patients is dangerous and distances should be as short as possible. 2,3 The same physical considerations are necessary for the operating theatre, which also should be adjacent to the laboratory. Bailout surgery may be required after complex catheter interventions.…”
Section: Locationmentioning
confidence: 99%
“…Should, for whatever reasons, co-location not be possible, then the time for transport should be short enough to enable prompt surgical or paediatric cardiac ICU support, as even during short transport complications can occur. 2,3 The German "gemeinsamer Bundesausschuss", the highest decision-making body for the joint self-administration of doctors, dentists, psychotherapists, hospitals, and health insurance funds in Germany, which is responsible for commissioning of services, has clearly stated that co-location at least within the same building is essential, 5 and commissioning of services has ceased for some services for the reason that these requirements were not fulfilled. The British…”
Section: Locationmentioning
confidence: 99%